The effects of storytelling on anxiety and sleep in hospitalized children with fracture: A randomized clinical trial - Leila Valizadeh; Azam Romouzi; Parvaneh Aghajari; Mohammad Asghari Jafarabadi (Kashan University of Medical Sciences, 2022)
Background: Hospitalization induces anxiety and causes sleep disorders in children. Objective: This study aimed to examine the effects of listening and reading a tale on anxiety and sleeping onset time (SOT) among hospitalized children with fracture. Methods: This randomized clinical trial was conducted on 102 children with extremity fracture in Shohada Hospital of Tabriz in 2018-2019. Subjects were recruited consecutively and randomly allocated into three groups: control, storytelling, and simultaneous listening to and reading a tale. The data were collected using a demographic information questionnaire: questions on SOT, heart rate, and the Reynolds and Richmond Children's Anxiety Questionnaire. One-way analysis of variance, paired t-test, Chi-square and Fisher's exact test, and analysis of covariance were used to analyze the data. Results: Mean SOT, mean anxiety, and mean pulse rate did not significantly differ between the three groups at baseline. After the intervention, the mean SOT and mean pulse rate decreased significantly in all three groups (P < 0.001); however, the between-group differences were not statistically significant (P > 0.50). The mean manifest anxiety did not change significantly in any of the groups (P > 0.05). Conclusion: Storytelling had no effect on anxiety, heart rate, and SOT of children with fractures. Further studies can help determine the best method of storytelling for children with fractures.